The mechanism and potential targets of class II HDACs in angiogenesis. Issue 4 (26th December 2017) - Hou, Fei; Li, Dandan; Yu, Honglian; Kong, Qingsheng
Abstract: Angiogenesis refers to the new blood vessels deriving from the existing blood vessels, and it is a complex regulatory process. Angiogenesis is associated with the normal development of the body and tumor growth and migration. The imbalance of histone deacetylase, as an epigenetic modification, could induce the production of diseases, such as cancer, metabolic diseases, etc., and it also plays an important role in angiogenesis. Many researches indicate that class II HDACs nuclear shuttle and its phosphorylation are necessary for the diseases and the protection of the collective itself. This paper will make a review for the relationship between II HDACs and angiogenesis under physiological and pathologic categories, looking forward to the disease treatment in the future. Abstract : Class II HDACs and its phosphorylation or nuclear shuttle is necessary for the protection of the individual. This paper will make a review about the relationship between II HDACs and angiogenesis, looking forward to the vascular related diseases treatment in the future.